(untitled) (Medical Forum Monthly, 2021)
Objective: To find the mutation in scarb1 gene that may be the cause of dyslipidemia in type 2 diabetes mellitus (T2DM). Study Design: A cross-sectional comparative study Place and Duration of Study: This study was conducted at the department of Biochemistry, Quaid e Azam Medical College, Bahawalpur from October 2020 to April 2021. Materials and Methods: A total 50 individuals (20 having T2DM and dyslipidemia, 20 with T2DM without dyslipidemia and 10 healthy individuals) were enrolled for this study. Informed consent from the study participants was taken. Nuclear DNA was extracted from the blood. Quality and quantity of DNA was checked by 1% agarose gel electrophoresis. Primers of exon 8 were designed by using primer 3 software. Sequencing PCR was performed. On the purified product of sequencing PCR mutational analysis was conducted. Results: In genotyping analysis no mutation was found but the single nucleotide polymorphism was detected in all groups. The detected polymorphism was rs5888 at c.1050 position. Group I patients were diabetic with the deranged lipid profile.18 patients of this group diagnosed with SNP. Group II individuals were diabetics with normal lipid profile and three patients from this group were diagnosed with SNP. The third group was of healthy individuals and two patients from this group were also detected with SNP. Exon-8 was used for study. This SNP was not lethal. The transition from T to C did not change the amino acid which is coded. In both the cases coded amino acid is Alanine. Conclusion: The SNP rs5888 was found in all the 3 groups of study. This alteration in nucleotide sequence is non-deleterious as the amino acid which is formed is alanine. This indicates that this polymorphism has no role in causing dyslipidemia in the diabetic individuals.